The South Atlantic Current Revisited: Description and Mesoscale Dynamics - Lapolli, Fabricio Rodrigues (2018)
Oceanic Gyres are the most conspicuous features in the Earth\'s ocean. They are ubiquitous to each basin and hemisphere. In the Atlantic Ocean, there is an uncanny symmetry between the North and South Atlantic Subtropical Gyres. Focusing on their poleward limits, we can think of them as virtually perfect analogues. However, while the North Atlantic Current has been extensively studied, the South Atlantic Current (SAC) still has been very little investigated and its knowledge presents crucial gaps on understanding it ocean\'s mesoscale variability and climate. Very little studies attempted so far to describe the SAC characteristics in terms of water mass properties and volume transports. In addition, there is the presence of recently described Saint Helen Current (StHC), which can be considered as the South Atlantic analogue of the Azores Current. The StHC has its formation tied with the Brazil Current (BC) retroflection. The SAC, on the other hand, is originated at the Brazil-Malvinas Confluence (BMC), and flows crossing zonally the Atlantic Basin. However, the presence of the northern branch of Antarctic Circumpolar Current (ACCn) (without an analogue in the northern hemisphere) brought a few additional challenges to studying the SAC. The ACCn can be thought as the Malvinas Current (MC) Extension, which exits the BMC region via the southern flank of the Zapíola Rise. In this work, we revisit the descriptive oceanography of the SAC system with newly developed climatologies (WOA13 and ARMOR3D) and seek to unravel the pattern associated with the current in the Southern limb of the region. Recent literature mentions that there is an important interplay between this three zonal jets as the cross the South Atlantic. However, only kinematics arguments were used to pinpoint this interplay so far. Hence, we opted to employ a statistical correlation method involving temperature, salinity and density vertical profiles (and consequently, T-S curves as well). We also computed volume transport values for the whole zonal domain across the South Atlantic Subtropical Gyre southern limb. In particular, at the longitude that it reaches the Mid-Atlantic Ridge, the major portion of the SAC veers south and merge almost completely with the ACCn. Its smaller northern the StHC. Near the eastern ocean border of the South Atlantic Ocean, the SAC-ACCn as well as a portion of the StHC traverse into the Indian Ocean. The combined analysis of geostrophic streamfunction fields and the temperature-density correlation diagrams do not show sufficient evidence for the StHC being an independent current, and not a branch of the SAC. Since there is also no study regarding the dynamics of the SAC we also constructed a linear QG instability model aiming to evaluate the current system mesoscale activity. We then analyzed the mesoscale activity of the SAC, and discovered that SAC is unstable throughout the whole path domain towards Africa. This instabilities, however, are found to be not as vigorous as the ACC. We also identify a shift in mesoscale vorticity wave regime as the SAC crosses the Mid-Atlantic Ridge. We found it to be less unstable than at the western side. We, however, could not identify the type of instabilities associated with the current. Therefore, we propose as sequential future work to further pursue investigation on the mesoscale dynamics of the ACCn-SAC-StHC system.